Acute canagliflozin treatment protects against in vivo myocardial ischemia–reperfusion injury in non-diabetic male rats and enhances endothelium-dependent vasorelaxation - Sayour, Alex Ali; Korkmaz-İçöz, Sevil; Loganathan, Sivakkanan; Ruppert, Mihály; Brune, Maik; Karck, Matthias; Szabó, Gábor (Journal of translational medicine, 2019)
The sodium–glucose cotransporter-2 (SGLT2) inhibitor canagliflozin has been shown to reduce major cardiovascular events in type 2 diabetic patients, with a pronounced decrease in hospitalization for heart failure (HF) especially in those with HF at baseline. These might indicate a potent direct cardioprotective effect, which is currently incompletely understood. We sought to characterize the cardiovascular effects of acute canagliflozin treatment in healthy and infarcted rat hearts.
Gesehen am 14.05.2019